2013
DOI: 10.17705/1pais.05201
|View full text |Cite
|
Sign up to set email alerts
|

The role of Social media during Queensland floods: An Empirical Investigation on the Existence of Multiple Communities of Practice (MCoPs)

Abstract: The notion of communities getting together during a disaster to help each other is common. However, how does this communal activity happen within the online world? Here we examine this issue using the Communities of Practice (CoP) approach. We extend CoP to multiple CoP (MCoPs) and examine the role of social media applications in disaster management, extending work done by Ahmed (2011). Secondary data in the form of newspaper reports during 2010 to 2011 were analysed to understand how social media, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(13 reference statements)
1
6
0
4
Order By: Relevance
“…Once the local usefulness of social media was understood, accepted and enacted in practice, social media was actualized as a boundary object‐in‐use – a catalyst of immersion that spans relational boundary. The actualization of social media as a catalyst of immersion is significant because during and after a crisis event, emotional support and companionship are critical to assist the victims in recovery (Perez‐Lugo, ; Ahmed & Sinnappan, ). In our case study, impacted communities in Thailand recognized the dialogic and open nature of social media and enacted it as a common space that allows for the accumulation of ‘human voices’, i.e., personal messages that engender emotional understanding and empathy in ways that the official statements cannot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the local usefulness of social media was understood, accepted and enacted in practice, social media was actualized as a boundary object‐in‐use – a catalyst of immersion that spans relational boundary. The actualization of social media as a catalyst of immersion is significant because during and after a crisis event, emotional support and companionship are critical to assist the victims in recovery (Perez‐Lugo, ; Ahmed & Sinnappan, ). In our case study, impacted communities in Thailand recognized the dialogic and open nature of social media and enacted it as a common space that allows for the accumulation of ‘human voices’, i.e., personal messages that engender emotional understanding and empathy in ways that the official statements cannot.…”
Section: Discussionmentioning
confidence: 99%
“…Twitter) for collective sense‐making during violent crises and suggested that microblogging technology provides a channel for connection and enables individuals to make sense of the chaos. Ahmed and Sinnappan () examined the use of social media in facilitating communication during the Queensland floods in 2010. Oh et al () examined how Twitter was used in social crises, with a particular emphasis on information quality issues and rumour.…”
Section: Social Media For Disaster Responsementioning
confidence: 99%
“…Recently, SNSs have been used after a variety of crises (e.g., Palen, Vieweg, Liu, & Hughes, 2009; Shklovski, Burke, Kiesler, & Kraut, 2010; Shklovski et al, 2008; Starbird & Palen, 2010; Taylor, Wells, Howell, & Raphael, 2012; Yanay, Benjamin, & Yamin, 2011), and support exchange of information in various ways, such as posting, linking, and texting (Oh, Agrawal, & Rao, 2013). SNSs can update the public on what is happening in real time and provide a platform for the public to show their supports for those affected (Ahmed & Sinnappan, 2013). Indeed, Taylor, Wells, Howell, and Raphael (2012) highlight the ability of SNSs to provide timely information about crises, enabling people to connect both to their friends and to the public.…”
Section: The Role Of Snss After Crisesmentioning
confidence: 99%
“…One reason that SNSs are increasingly popular is they enable people to contribute and respond at the same time (Ahmed & Sinnappan, 2013). In other words, SNSs support interactivity and people can post and comment.…”
Section: The Role Of Snss After Crisesmentioning
confidence: 99%
“…Previous research into environmental disasters has shown evidence that sourcing community generated information about local action from social media and crowd-sourcing platforms is possible [23][24][25][26], and has been employed as a live data source in several natural disasters [27,28]. Posthoc analysis has also revealed that useful data can be drawn from these sources [23,29,30], including levels of community resilience [31].…”
Section: Introductionmentioning
confidence: 99%